Le traitement du discours indirect libre flaubertien dans le film de Claude Chabrol Madame Bovary - Gacoin-Marks, Florence (Vestnik za tuje jezike, 2013)
The paper deals with the transformation of Flaubert's free indirect speech in the film Madame Bovary by Claude Chabrol. Conversion of free indirect speech into direct speech or into narration by an external narrator (voice-over) cannot be avoided, it does, however, pose many problems because of the potential ambiguousness (polyphony) of free indirect speech. In such cases, Chabrol often finds effective solutions which bring the film closer to Flaubert's style. Nevertheless, it remains clear that film adaptations of literary masterpieces entail serious losses. Therefore teachers must convince students that film adaptations of high-quality literature can never replace literary works themselves. Literature and film are two different media, based on distinct types of artistic expression, and should be presented as such to students. As a consequence, film adaptations of literary masterpieces should not uncritically be considered as the most suitable material in all teaching contexts.
Keywords: Flaubert, Gustave, 1821-1880; "Madame Bovary"; Chabrol, Claude, 1930-2010; francoski roman; French literature; francoska književnost; francoski film; literatura in film; polpremi govor